2020
DOI: 10.1093/aob/mcaa189
|View full text |Cite
|
Sign up to set email alerts
|

Frugivory and seed dispersal in a hyperdiverse plant clade and its role as a keystone resource for the Neotropical fauna

Abstract: Background and aims Much of our understanding of the ecology and evolution of seed dispersal in the Neotropics is founded on studies involving the animal-dispersed, hyper-diverse plant clade Miconia (Melastomataceae). Nonetheless, no formal attempt has been made to establish its relevance as a model system or indeed provide evidence of the role of frugivores as Miconia seed dispersers. Methods We built three Miconia databases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 181 publications
(246 reference statements)
0
5
0
Order By: Relevance
“…The potential to interact commensally or compete with ants has a strong phylogenetic structure and was held by the ancestors of birds. The fact that several extant phylogenetic distant reptilian taxa had been reported to have commensal [ 71 ] and competitive [ 72 ] interactions with ants might suggest that even the reptilian ancestor of birds already had that proneness to interact with ants. However, although the birds ‘ancestor engaged in commensalism and competition with ants, many avian families currently do not, which suggests either that some bird families may have loss that capacity while radiating because selection led then to exploit niches where they do not coincide with ants, or that these families were less studied.…”
Section: Discussionmentioning
confidence: 99%
“…The potential to interact commensally or compete with ants has a strong phylogenetic structure and was held by the ancestors of birds. The fact that several extant phylogenetic distant reptilian taxa had been reported to have commensal [ 71 ] and competitive [ 72 ] interactions with ants might suggest that even the reptilian ancestor of birds already had that proneness to interact with ants. However, although the birds ‘ancestor engaged in commensalism and competition with ants, many avian families currently do not, which suggests either that some bird families may have loss that capacity while radiating because selection led then to exploit niches where they do not coincide with ants, or that these families were less studied.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings imply that the vertical stratification of interactions is caused by differences in the locomotory and foraging behavior of different types of frugivores. While prior studies have shown how fruit nutritional (Pizo et al, 2021) or morphological traits such as seed size (Messeder et al, 2020) are important drivers of community‐wide interaction patterns, in Cactaceae it is also the distance of fruits to the ground that structure the use by different frugivore taxa. Our study reinforces the idea that cacti are keystone species in semiarid regions given their high fruit production and extended availability across both dry and wet seasons.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, entire communities could be reshaped following shifts in plant reproductive phenology, for example where coflowering patterns within the community are altered [55]. Particularly in the case of Miconia species, their fruits and seeds are usually dispersed by a bunch of frugivorous [56], and temporal alterations in the production of fruits and seeds may also impact animals that depend on it for food [50], likely leading to trophic mismatches and cascading effects on communities [46], in spite of possible network resilience by rewiring.…”
Section: Plos Onementioning
confidence: 99%